Prevalence of loneliness and associations with health behaviours and body mass index in 5835 people living with and beyond cancer: a cross-sectional study - Susan Smith; Phillippa Lally; Andrew Steptoe; Yanaina Chavez-Ugalde; Rebecca J Beeken; Abi Fisher (BMC, 2024)
Abstract Background A cancer diagnosis and its treatment may be an especially isolating experience. Despite evidence that positive health behaviours can improve outcomes for people living with and beyond cancer (LWBC), no studies have examined associations between loneliness and different health behaviours in this population. This study aimed to describe the prevalence of loneliness in a large sample of UK adults LWBC and to explore whether loneliness was associated with multiple health behaviours. Methods Participants were adults (aged ≥ 18 years) diagnosed with breast, prostate or colorectal cancer who completed the Health and Lifestyle After Cancer Survey. Loneliness was reported using the UCLA loneliness score, dichotomised into higher (≥ 6) versus lower (< 6) loneliness. Engagement in moderate-to-vigorous physical activity, dietary intake, smoking status, alcohol use, and self-reported height and weight were recorded. Behaviours were coded to reflect meeting or not meeting the World Cancer Research Fund recommendations for people LWBC. Logistic regression analyses explored associations between loneliness and health behaviours. Covariates were age, sex, ethnicity, education, marital status, living situation, cancer type, spread and treatment, time since treatment, time since diagnosis and number of comorbid conditions. Multiple imputation was used to account for missing data. Results 5835 participants, mean age 67.4 (standard deviation = 11.8) years, completed the survey. 56% were female (n = 3266) and 44% (n = 2553) male, and 48% (n = 2786) were living with or beyond breast cancer, 32% (n = 1839) prostate, and 21% (n = 1210) colorectal. Of 5485 who completed the loneliness scale, 81% (n = 4423) of participants reported lower and 19% (n = 1035) higher loneliness. After adjustment for confounders, those reporting higher levels of loneliness had lower odds of meeting the WCRF recommendations for moderate-to-vigorous physical activity (Odds Ratio [OR] 0.78, 95% Confidence Internal [CI], 0.67, 0.97, p =.028), fruit and vegetable intake (OR 0.81, CI 0.67, 1.00, p =.046), and smoking (OR 0.62, 0.46, 0.84, p =.003). No association was observed between loneliness and the other dietary behaviours, alcohol, or body mass index. Conclusions Loneliness is relatively common in people LWBC and may represent an unmet need. People LWBC who experience higher levels of loneliness may need additional support to improve their health behaviours.